The impact of the UK 'two-week rule' on stage-on-diagnosis of oral cancer and the relationship to socio-economic inequalities. (June 2019) - Langton, Steve; Lowe, Derek; Rogers, Simon N; Plüddemann, Annette; Bankhead, Clare
Highlights: Assessment of stage on diagnosis of 1483 oral cancers 1992–2012, before and after the UK 2000 Cancer Plan. A lower percentage of oral cancers present late following the Cancer Plan and 'two week rule' (TWR). Decline in late cases started before the TWR and has continued with no significant rate alteration. Stage improvement rate was highest for most deprived; however, deprivation inequality persists. Abstract: Background: The 'two-week rule' (TWR) fast-track cancer referral system for head and neck cancers was introduced by the UK government in 2000, to facilitate earlier diagnosis. However, little work has compared stage on diagnosis of cancer before and after the implementation of the system. Objectives: Describe the presentation of oral cancer in Merseyside from 1992 to 2012. To evaluate whether stage on presentation has improved after the introduction of the TWR using data from a clinical database in Merseyside 1992–2012. To assess the relationship between stage on presentation and social deprivation 1992–2012. To assess the change in presentation for different sites within the oral cavity. Method and setting: Patients were identified using the Aintree (Liverpool) head and neck oncology database, containing all diagnoses of oral squamous cell carcinoma (SCC) between 1992 – 2012. Cancers were clinically staged using the American Joint Committee on Cancer (AJCC) stage groupings and divided into 'early' (stage 1 and 2) and 'late' (stage 3 and 4). Index of Multiple Deprivation (IMD) 2004 data were derived from patient postcodes. Appropriate regression analyses were undertaken. Results: 1485 consecutive patients diagnosed were studied. Median (IQR) age was 63 (55–73) years and 61% were male. 36% of cancers were located on anterior 2/3rds tongue, 30% floor of mouth, and 34% elsewhere. 'Late' tumour presentation was 52% (95%CI 46.8–56.4%) for 1992–2000, and 44% (95%CI 41.4–47.5%) for 2001–2012 (P = 0.01). Joinpoint regression analysis of 'late' presentation indicated a steady fall 1992–2012, at an annual percentage decrease of 1.27% (95% CI −2.3 to −0.2). No statistically significant change in trend was identified either overall or within deprivation groups following the TWR. For patients in 'more deprived' neighbourhoods, 'late' tumour presentation was: 56% and 47%; in 'less deprived' areas: 48% and 42%, before and after the introduction of the TWR, respectively. Year of diagnosis, tumour site and IMD2004 were significantly associated with 'late' presentation, and location of tumour was also associated with time period and IMD2004. Main conclusions: Stage on presentation improved between 1992–2012. Joinpoint analysis showed no significant change in trend following the introduction of the TWR. The rate of improvement was highest for most deprived; nevertheless, deprivation inequality persists and this should be a focus of further initiatives and research.